Offerkastet som gårdagens och morgondagens källa för skuld, sorg och skadeprevention - Lundälv, Jörgen (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2004)
Concepts such as victim-blaming, grief and injury prevention have become important in our risk society. To remember victims in traffic accidents (e.g. injury events in traffic environments), family members and members from the victim's social network, put flowers, photography, decoration, candle wax at the scene of the accident. If mass media reported this signs from the traffic environments when the injury prevention should be better in the future. The aim of this article is to discuss some perspectives of the scene of accident as a place and source of blame, grief but also injury prevention.